Effect of geometry of underground structure and electrode on electrical resistance measurement: A numerical study - Kim, Tae Young; Ryu, Hee Hwan; Kang, Meiyan; Choi, Suyoung; Chong, Song Hun (Geomechanics and Engineering, 2024)
Recently, electrical resistivity surveys have been used to obtain information related to underground structures including burial structure type and depth. However, various field conditions hinder understanding measured electrical resistance, and thus there is a need to understand how various geometries affect electrical resistance. This study explores the effect of geometric parameters of a structure and electrodes on electrical resistance in the framework of the finite element method. First, an electrical resistance module is developed using the generalized mesh modeling technique, and the accuracy of the module is verified by comparing the results with the analytical solution for a cylindrical electrode with conical tip. Then, 387 cases of numerical analysis including geometric parameters of a buried structure and electrodes are conducted to quantitatively estimate the detection depth under a steady-state current condition. The results show that electrical resistance is increased as (1) shallower burial depth of structure, (2) closer distance between ground electrode and structure, (3) longer horizontal electrode distance. In addition, the maximum detection depth corresponding to converged electrical resistance is deeper as (4) closer distance between ground electrode and structure, (5) shorter horizontal electrode distance. The distribution of the electric potential around the electrodes and underground structure is analyzed to provide a better understanding of the measured electrical resistance. As engineering purpose, the empirical equation is proposed to calculate maximum detection depth as first approximation.
Keywords: Cylindrical electrode with conical tip; Cylindrical electrodes; Detection depths; Electrical resistance module; Electrical resistances; Electrical resistivity survey; Generalized mesh modeling technique; Maximum detection depth; Mesh modeling; Modelling techniques; Resistivity surveys; cylindrical electrode with conical tip; electrical resistance module; electrical resistivity survey; generalized mesh modeling technique; maximum detection depth